Inducing low-carbon investment in the electric power industry through a price floor for emissions trading - Alexander Brauneis; Michael Loretz; Roland Mestel; Stefan Palan (Fondazione Eni Enrico Mattei (FEEM), 2011)
Uncertainty about long-term climate policy is a major driving force in the evolution of the carbon market price. Since this price enters the investment decision process of regulated firms, this uncertainty increases the cost of capital for investors and might deter invest-ments into new technologies at the company level. We apply a real options-based approach to assess the impact of climate change policy in the form of a constant or growing price floor on investment decisions of a single firm in a competitive environment. This firm has the opportunity to switch from a high-carbon dirty technology to a low-carbon clean technology. Using Monte Carlo simulation and dynamic programming techniques for real market data, we determine the optimal CO2 price floor level and growth rate in order to induce investments into the low-carbon technology. We show these findings to be robust to a large variety of input parameter settings.
Keywords: D81; O38; Q55; 330; Carbon price; price floor; technological change; investment decision; real option approach